Association of Metabolic Dysfunction-Associated Fatty Liver Disease and Liver Stiffness With Bone Mineral Density in American Adults - Li, Hejun; Luo, Hengcong; Zhang, Ying; Liu, Lisi; Lin, Rong (Frontiers in Endocrinology, 2022)
Contest: The relationship between metabolic dysfunction-associated fatty liver disease (MAFLD) and liver stiffness and bone mineral density (BMD) remains unclear. Objectives: We aimed to investigate the association between MAFLD and liver stiffness and BMD in the United States population. Methods: A cross-sectional study among 2031 participants over 50 years old in the National Health and Nutrition Examination Survey (NHANES) 2017-2018 was performed. All patients underwent vibration controlled transient elastography (VCTE) and dual-energy x-ray absorptiometry (DXA). The linear and logistic regression model were used to analyze the association between the MAFLD and liver stiffness and osteoporosis, with adjustments for known covariates. Furthermore, the sensitive analyses were conducted to explore the relationship between MAFLD and liver stiffness and whole osteoporosis (include femoral and lumbar osteoporosis). Results: MAFLD was prevalent in the study population, with a prevalence of 50.9% for men and 40.7% for women. The multiple linear models demonstrated positive associations between MAFLD and liver stiffness and total femur BMD, femur neck BMD, trochanter BMD, intertrochanter BMD. In multiple logistic regression models, both MAFLD and significant liver fibrosis were negatively associated with femoral osteoporosis (OR=0.41, 95% CI: 0.27 to 0.63; OR=0.67, 95% CI: 0.33-1.37, respectively). Nonetheless, when BMI was adjusted, the association between MAFLD and liver stiffness and osteoporosis became insignificant. Besides, as showed in the sensitive analyses, the relationship between MAFLD and liver stiffness and whole osteoporosis were stable. Conclusions: These results suggest that MAFLD and liver stiffness were associated with higher femoral and lumbar bone mineral density in individuals aged over 50 years. But the results may be confounded by BMI.